PROKRASTINASI AKADEMIK PADA MAHASISWA BIDIKMISI: AREA DAN FAKTOR PROKRASTINASI - Annisa Dafa Rahmadanti; Fitriani Yustikasari Lubis; Whisnu Yudiana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
This study aimed to describe academic procrastination behavior in Bidikmisi Scholarship Program awardees based on the academic area and factors of academic procrastination. The research method used is descriptive research with a quantitative approach. The data collection technique used a questionnaire measuring tool Procrastination Assessment Scale-Student (PASS) which has been adapted to Indonesian.. This study was distributed online through an electronic survey using a Google Form in one month in August 2022. This study consisted of 353 students with the majority of participants were female (66.57%), taken through the snowball sampling techniques. This study used the Scale-Content Validity Index (S-CVI) to calculate validity and Cronbach's Alpha to calculate reliability. Data were analyzed in descriptive statistics using the IBM SPSS Statistics version 25 to obtain the mean and standard deviation.The results showed that Bidikmisi Scholarship Program awardees tended to procrastinate in studying for an exam and least procrastinate in attending meetings. It also found that evaluation anxiety, perfectionism, and the tendency to feel overwhelmed were the most frequent factors for students to procrastinate. Meanwhile, the fear of success, rebellion against control, and peer influence were the least frequent factors that describe why students procrastinate.